Economics of Milk Production Among Member and Non-Member Families of Dairy Cooperatives in Jaipur (Rajasthan) - Tanwar, P S; Kumar, Yogendra; Sankhala, Gopal (Indian Journal of Dairy Science, 2012)
Study was conducted to estimate the economics of milk production among different categories of members and non-members families of dairy co-operatives based on personal interview method. An analysis of data from 240 families (120 household under each category) revealed that overall gross maintenance cost per animal per year was higher (Rs. 21532.81) in members families in comparison to non-members families (Rs. 19768.30). Maximum gross maintenance cost was on small farmers and minimum was on landless farmers in both the categories. The share of variable and fixed cost in total maintenance cost was (82.36% and 17.64%) in members families and almost same in case of non-members families (82.95% and 17.05%). The cost of feed, fodder and concentrate was main component in gross maintenance cost in both the categories. The overall cost per liter of milk was lower (Rs.10.47) in members families than non-members families (Rs.11.29). The size of land holding showed negative relationship with cost of milk production. Overall net return per animal per year was higher in members households in comparison to non-members households. Overall net profit per liter of milk was Rs. 4.73 for members households, while it was Rs. 2.01 on non-members households. The overall average income per rupee of investment was higher ( Rs.1.45) in members families than non-members families (Rs. 1.18).